2023
DOI: 10.1038/s41598-022-26896-3
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β neutralization prevents diastolic dysfunction development, but lacks hepatoprotective effect in an aged mouse model of NASH

Abstract: Interleukin-1β (IL-1β) is a key mediator of non-alcoholic steatohepatitis (NASH), a chronic liver disease, and of systemic inflammation-driven aging. IL-1β contributes to cardio-metabolic decline, and may promote hepatic oncogenic transformation. Therefore, IL-1β is a potential therapeutic target in these pathologies. We aimed to investigate the hepatic and cardiac effects of an IL-1β targeting monoclonal antibody in an aged mouse model of NASH. 24 months old male C57Bl/6J mice were fed with control or choline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 76 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…Similarly to our previous publication [16], we established that IL-1β is relevant not only for the hepatic pathophysiology of NASH, but it is highly expressed in cardiovascular system as well. This highlights that inflammation could be an important therapeutical target, which is further supported by the CANTOS trial [72].…”
Section: Nash Triggers Cardiac Hypertrophy Fibrosis and Inflammationsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly to our previous publication [16], we established that IL-1β is relevant not only for the hepatic pathophysiology of NASH, but it is highly expressed in cardiovascular system as well. This highlights that inflammation could be an important therapeutical target, which is further supported by the CANTOS trial [72].…”
Section: Nash Triggers Cardiac Hypertrophy Fibrosis and Inflammationsupporting
confidence: 77%
“…NASH is characterized by hepatic steatosis with displaced nuclei, extensive inflammation, and fibrosis [15]. In our previous studies, we already showed that 8 weeks of feeding with CDAA diet effectively induces classical histologic signs of NASH [14,16] (Fig. 1A); nonetheless, we performed histologic and molecular analyses to evidence the development of NASH in the present cohort.…”
Section: Cdaa Diet Induces Key Histopathologic Features Of Nashmentioning
confidence: 67%
“…The IL-1 family cytokines, especially IL-1β, are key mediators in the progression of MASLD to its more severe form, NASH. IL-1β leads to hepatic triglyceride accumulation (steatosis) and is associated with increased pro-inflammatory cytokine expression in MASLD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between CTLA4 and IL-1β/sTNFR-1 remains unclear. However, IL-1β secretion is regulated by CTLA4-Ig fusion protein [ 30 ], and the administration of IL-1β inhibitors in a mouse model of hepatitis upregulates the expression of PD-1 and CTLA4 in the liver [ 31 ]. Moreover, TNFR-1 contributes to the termination of immune responses through its ability to induce apoptosis, and the possible involvement of CTLA4 in these apoptotic pathways has also been reported [ 32 ].…”
Section: Discussionmentioning
confidence: 99%